PENERAPAN RESTORATIVE JUSTICE DALAM KASUS PENGANIAYAAN PADA KEJAKSAAN NEGERI DELI SERDANG - Daniel Octavianus Sinaga; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
In Indonesia, in the implementation of punishments or crimes against perpetrators of abuse cases, law enforcers are more likely to process their crimes by ensnare and sentence the perpetrators to prison regardless of how the abuse case occurred, in which case law enforcers can make restorative efforts. justice with mediation bridges (mediates) the parties between the perpetrators and the victims without having to carry out a criminal law process but by imposing sanctions/punishments on compensation or medical expenses that have been suffered by the victims. The crime of persecution in the application of restorative justice at the Deli Serdang District Attorney level is a form of crime of persecution that can be applied to a restorative justice settlement, including: minor maltreatment, maltreatment of child perpetrators, abuse in which the perpetrator and the victim have an emotional relationship. The inhibiting factors in solving the crime of persecution through the application of restorative justice at the Deli Serdang District Attorney are influenced by law enforcement factors, legal substance factors, and cultural factors. The application of restorative justice for the settlement of the crime of persecution at the Deli Serdang District Attorney level is based on Prosecutor's Regulation No. 15 of 2020. Through the Prosecutor's Regulation, it is stated that the Public Prosecutor's authority is to close cases for the sake of law on the grounds that there has been a settlement of cases outside the court (afdoening buiten process). The terms, procedures, and mechanisms for conciliation efforts in ending prosecutions based on restorative justice by the Deli Serdang District Attorney are regulated by Prosecutor's Regulation No. 15 of 2020.